Supporting mothers to bond with their newborn babies: Strategies used in a neonatal intensive care unit at a tertiary hospital in Malawi - Phuma-Ngaiyaye, E.; Kalembo, Fatch (2016)
AbstractBackground Maternal–newborn bonding during the first hours of is crucial to infant development. Effective bonding requires that newborn baby and mother be close to each another, so that the baby can signal his/her needs and the mother can respond. However, normal bonding process is hindered by illness, as the infants will be separated from their mothers and admitted to neonatal intensive care units. No study has explored the techniques applied by nurses and midwives to facilitate bonding between mothers and their sick newborn babies admitted in neonatal intensive care units in Malawi. Purpose This study aimed to investigate the strategies for supporting maternal–newborn bonding for mothers whose neonates were admitted to an intensive care unit at a tertiary hospital in Malawi. Methods An explorative qualitative design was used, and 15 participants (10 mothers and five nurses/midwives) were recruited. Data were collected by conducting in-depth interviews. Audio recorded data were transcribed verbatim and analyzed by utilizing ATLAS. ti version 7 in accordance with Hennink's stages of content analysis. Results It was showed that nurses and midwives used different approaches to facilitate maternal–newborn bonding. The responses revealed two major themes: mother–newborn interaction and mother–nurse/midwife interaction. Mother–newborn interaction involved breastfeeding and maternal involvement in newborn care, whereas mother–nurse/midwife interaction involved effective communication and psychosocial support. Maternal–newborn bonding promotes a mother's successful transition into motherhood, nurses and midwives should actively initiate strategies facilitating early maternal–newborn bonding.